2018
DOI: 10.1021/acs.langmuir.8b00009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Emulsion-Templated Magnetic Porous Hydrogel Beads and Their Application for Catalyst of Fenton Reaction

Abstract: The pristine FeO nanoparticle (FeNP) is supposed to be a good catalyst of Fenton processes which have shown significant potential for water purification. Herein the magnetic macroporous hydrogel beads, having an open-cell structure, were synthesized by sedimentation polymerization of pristine FeNP stabilized oil-in-water high internal phase emulsions. The effects of the FeNP amount, internal phase fraction, and the costabilizer Tween85 concentration on the structure, such as interconnecting degree, void size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 62 publications
0
48
1
Order By: Relevance
“…Emulsion‐templated porous materials have been shown to be useful for a wide range of applications . Especially on water/oil separation due to their tunable hydrophobic–oleophilic or hydrophilic–oleophobic properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emulsion‐templated porous materials have been shown to be useful for a wide range of applications . Especially on water/oil separation due to their tunable hydrophobic–oleophilic or hydrophilic–oleophobic properties .…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION Emulsion-templated porous materials have been shown to be useful for a wide range of applications. [1][2][3][4][5][6][7] Especially on water/oil separation due to their tunable hydrophobic-oleophilic or hydrophilic-oleophobic properties. [8][9][10] In this method, high internal phase emulsions (HIPEs), having an internal phase volume fraction of more than 74%, were normally used as templates to prepare porous polymer materials (so called polyHIPEs).…”
mentioning
confidence: 99%
“…PolyHIPEs (PHs) are macroporous polymers synthesized within the continuous phase of high internal phase emulsions (HIPEs), emulsions consisting of over 74% dispersed phase by volume. PHs have drawn considerable attention, due to their potential applications in controlled release, encapsulation, catalyst support, absorption, adsorption, tissue engineering, and water‐efficiency enhancer in fighting fires . For these applications, amphiphilicity is an integral component.…”
Section: Introductionmentioning
confidence: 99%
“…Macroporous polymers have extensive applications in many elds, such as tissue engineering scaffolds, [1][2][3][4] controlled release, [5][6][7][8][9] ion adsorption, 10-13 separation 14,15 and supports for catalysis. [16][17][18][19][20] These applications normally require porous polymers with an open-cell structure. One of the effective methods to synthesize macroporous polymers is the use high internal phase emulsion (HIPE) templates whose dispersed phase exceeds 74 vol%.…”
Section: Introductionmentioning
confidence: 99%
“…50 We also reported a series of open-cell porous polymers based on Pickering HIPEs by adding a small amount ($1.0%) of surfactant to the emulsion before curing. 17,[53][54][55] The mechanism of formation of the closed-cell structure suggested that a thicker particle layer around the droplets formed very stable emulsion lms which do not easily rupture during or aer polymerization, so the closed-cell pore structure exhibits poly-Pickering-HIPEs. 56,57 Furthermore, the formation of interconnected pores in the poly-Pickering-HIPEs following addition of a small amount of surfactant was assumed to proceed as follows.…”
Section: Introductionmentioning
confidence: 99%